2020
DOI: 10.1109/access.2020.2972739
|View full text |Cite
|
Sign up to set email alerts
|

Filtering Power Amplifier With Up to 4th Harmonic Suppression

Abstract: Unlike conventional conception that power amplifier and filter are regarded as two separate components and designed separately, this paper presents a high efficiency power amplifier with filtering capability, which is called filtering power amplifier. The proposed power amplifier integrates a bandpass filter as output matching network so that entire size is reduced to some extent. The filter will play the role of filtering and impedance matching simultaneously, and thus high-order harmonics are suppressed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A microstrip hairpin BPF is proposed as OMN of PA in Haider et al, 20 which improves the performance of PA at the target band. Su et al 21 showed that both the input matching network (IMN) and OMN of PA use a BPF impedance converter, which perfectly matched the fundamental and second harmonic of the PA. Qui and Xiao 22 showed that the FPA has good out‐of‐band performance, as high as 46.2 dB suppression can be achieved and extended over the fourth harmonic. Also, retain the advantages of high efficiency and output power.…”
Section: Introductionmentioning
confidence: 99%
“…A microstrip hairpin BPF is proposed as OMN of PA in Haider et al, 20 which improves the performance of PA at the target band. Su et al 21 showed that both the input matching network (IMN) and OMN of PA use a BPF impedance converter, which perfectly matched the fundamental and second harmonic of the PA. Qui and Xiao 22 showed that the FPA has good out‐of‐band performance, as high as 46.2 dB suppression can be achieved and extended over the fourth harmonic. Also, retain the advantages of high efficiency and output power.…”
Section: Introductionmentioning
confidence: 99%
“…Harmonic-suppressing PAs (HS-PA) obtained through various design methods are presented in previous studies. [8][9][10][11][12][13][14] Harmonic cancelation through harmonic injection is reported in Singhal and Rawat, 8 of which the hardware configuration is schematically shown in Figure 1A. The DSP technique renders harmonic suppression over large bandwidth; however, the hardware overhead is Index Terms: Efficiency, harmonic suppression, matching network, output power, power amplifier complex.…”
Section: Introductionmentioning
confidence: 99%
“…Cancelation of even-order harmonics over wideband is realized in the push-pull strategy; however, bulky circuit configuration is required and the odd-order harmonics cannot be suppressed. Harmonic suppression by integrating a bandpass filer (BPF) cascaded after the PA's output matching network (OMN) is reported in Raghavan et al, 10,11 of which the circuit configuration is schematically shown in Figure 1C. The deployment of the standalone BPF in the PA does not only increase the circuit size but also causes extra insertion loss and hence decreases the PA efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The filtering power amplifier (FPA) in Ref. 18 can achieve up to 46.2 dB of suppression and extend to the fourth harmonic, also retains the advantages of high efficiency and output power. A stub loaded parallel‐coupled lines microstrip BPF proposes in Ref.…”
Section: Introductionmentioning
confidence: 99%